Implementasi Kebijakan Kartu Identitas Anak di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Morowali Utara - Simuru, Lisbeth; Mufti, Moh. Irfan; Nasrullah (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the implementation of the Child Identity Card (KIA) policy at the Population and Civil Registration Office (Disdukcapil) of North Morowali Regency using George C. Edward III’s policy implementation framework, which emphasizes four key variables: communication, resources, implementer disposition, and bureaucratic structure. The research employs a descriptive qualitative method through in-depth interviews, direct observations, and official document analysis, involving policy implementers as key informants. The findings indicate that the implementation of the KIA policy performs relatively well in terms of implementer disposition, reflected in the high commitment, integrity, and initiative demonstrated by staff in optimizing service delivery. The bureaucratic structure also supports implementation through clear, transparent, and adaptive SOPs, as well as effective cross-sector coordination between Disdukcapil, hospitals, and community health centers through integrated services. However, the effectiveness of implementation is hindered by weak communication, as socialization efforts fail to reach all communities evenly due to budget limitations and low digital literacy in remote areas. Additionally, resource constraints—including limited outreach budgets, insufficient personnel, and frequent technical issues with KIA printing equipment—pose significant challenges. This study concludes that the success of the KIA policy implementation heavily depends on strengthening financial support, improving technical capacity, and adapting communication strategies to the geographic conditions and community characteristics of North Morowali.